2022
DOI: 10.1177/23743735221107237
|View full text |Cite
|
Sign up to set email alerts
|

“I was Unsure at First”: A Qualitative Evaluation of Patient Perceptions of VA Clinical Video Telehealth Visits in the V-IMPACT Program

Abstract: Virtual Integrated Multi-Site Patient Aligned Care Team (V-IMPACT) was a Veterans Health Administration (VHA) initiative created to increase access to primary care for Veterans through Clinical Video Telehealth (CVT) appointments. Between January and August 2019, we conducted 48 semi-structured qualitative interviews with Veterans who had a V-IMPACT appointment. Many participants shared feelings of skepticism before their first appointments but for some, their opinions changed. Veterans talked about how their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Although it is not clear whether lower care utilization was driven by patients, practitioners, or systemic barriers, prior studies of diabetes telemedicine have found similar results. 13,48,49 Additionally, differences in patientpractitioner communication via telemedicine, including difficulty building rapport, 50,51 may lead to differences in both patient self-management and practitioner treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear whether lower care utilization was driven by patients, practitioners, or systemic barriers, prior studies of diabetes telemedicine have found similar results. 13,48,49 Additionally, differences in patientpractitioner communication via telemedicine, including difficulty building rapport, 50,51 may lead to differences in both patient self-management and practitioner treatment decisions.…”
Section: Discussionmentioning
confidence: 99%